EFEK METANOL KADAR RENDAH TERHADAP TORSI MESIN DIESEL DENGAN SISTEM HOT EGR - Yafid Effendi (Universitas Muhammadiyah Tangerang, 2019)
One type of motorized vehicle that is very suitable for transportation and heavy equipment vehicles is diesel engines, because of its high combustion efficiency, reliability, fuel flexibility, and low fuel consumption make diesel widely used in several countries. Lowgrade methanol mixtures and jatropha are used as alternative fuels. This study aims to study the effect of low purity methanol mixture and jatropha on torque in Isuzu 4JB1 diesel engine direct injection with Hot EGR (Exhaust Gas Recirculation) system using a mixture of biodiesel fuel, low grade methanol and jatropha. The low purity methanol used has a water content of 24.88% based on volume. The ratio of biodiesel, methanol and jatropha mixture used is D85LPM5J10, D80LPM10J10, D75LPM15J10, D75LPM5J20, D70LPM10J20, D65LPM15J20, D65LPM5J30, D60LPM10J30 and D55LPM15J30. EGR openings varied from 0%, 25%, 50%, 75% and 100%. Testing is carried out at a constant rotation of 2000 rpm and given a load of 25%, 50%, 75% and 100%. This study uses dynamite Land & Sea dynamometer. The experimental results show that the EGR Effect can increase the torque value. Torque values tend to decrease when using a mixture of fuels compared to D100. At low loads (25%) there is an increase in the Torsi value for the fuel mixture D85LPM5J10, D80LPM10J10, D70LPM10J20 and D55LPM15J30 of 12.03%, 7.50%, 5.01%, and 5.97%.Keywords: Metanol, Torsi, Mesin, Diesel, EGR